2015
DOI: 10.1016/j.gca.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of salinity on hydrogen isotope fractionation in Rhizophora mangroves from Micronesia

Abstract: Please cite this article as: Nemiah Ladd, S., Sachs, J.P., Influence of salinity on hydrogen isotope fractionation in Rhizophora mangroves from Micronesia, Geochimica et Cosmochimica Acta (2015), doi: http://dx. AbstractHydrogen isotope ratios ( 2 H/ 1 H or δ 2 H) of plant leaf waxes typically covary with those of precipitation, and are therefore used as a proxy for past hydrologic variability. Mangroves present an important exception to this relationship, as salinity can strongly influence 2 H fractionation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 82 publications
1
26
0
Order By: Relevance
“…We separate convergence zone from El Niño-driven changes and observe substantial fluctuations even in the absence of perturbations as large as current anthropogenic forcing. it increases by 0.7-1.7‰ (13,16 Poza de las Diablas sediments were pink cyanobacterial deposits and contained few lithological changes between the sedimentwater interface and ∼340-cm depth (Fig. S2).…”
Section: Significancementioning
confidence: 99%
“…We separate convergence zone from El Niño-driven changes and observe substantial fluctuations even in the absence of perturbations as large as current anthropogenic forcing. it increases by 0.7-1.7‰ (13,16 Poza de las Diablas sediments were pink cyanobacterial deposits and contained few lithological changes between the sedimentwater interface and ∼340-cm depth (Fig. S2).…”
Section: Significancementioning
confidence: 99%
“…This is indicative of very limited evapotranspiration. Slightly depleted δ 2 H leaf values relative to δ 2 H xylem (i.e., small, negative ε l/x values) have previously been reported for some trees in Rhizophora mangroves (Ladd and Sachs, 2015). Ladd and Sachs (2015) ascribed this to the high ambient relative humidity, resulting in a small vapor pressure gradient across the leaf surface (see also Helliker and Ehleringer, 2000;Farquhar et al, 2007).…”
Section: Parameters Affecting Xylem-to-leaf Deuterium Enrichmentmentioning
confidence: 83%
“…Slightly depleted δ 2 H leaf values relative to δ 2 H xylem (i.e., small, negative ε l/x values) have previously been reported for some trees in Rhizophora mangroves (Ladd and Sachs, 2015). Ladd and Sachs (2015) ascribed this to the high ambient relative humidity, resulting in a small vapor pressure gradient across the leaf surface (see also Helliker and Ehleringer, 2000;Farquhar et al, 2007). The atypical ε l/x values of the two Capparaceae in this study are possibly associated with their xerophytic traits, in particular the waxy appearance of the leaves in many species of this family (Elffers et al, 1964).…”
Section: Parameters Affecting Xylem-to-leaf Deuterium Enrichmentmentioning
confidence: 83%
“…In addition, Duarte et al (2018) recently showed that Red Sea seagrass and macroalgae have distinct δ 2 H signatures and that the combination of δ 2 H and δ 13 C holds promise to discriminate these carbon sources in C org sediment stocks. Several factors such as photosynthesis, lipid content, isotopic discrimination during water uptake, biochemical and biophysical processes, and environmental seasonality allow differentiation of δ 2 H values in primary producers Ladd and Sachs, 2015;Adame et al, 2016).…”
Section: Recent Developments In Tracing Carbon Provenancementioning
confidence: 99%